Management of infected nonunions of the femur and tibia with compression-distraction osteogenesis coupled with modern methods at a tertiary military establishment: a prospective case series. Issue 1 (January 2021) - Kaul, Rajiv; Akhoon, Neha; Mugdum, Girish; Prasad, Manish
Abstract : Background: Infected nonunions pose a daunting challenge to any orthopaedic surgeon. The essence of treatment is a radical debridement for eradication of infection coupled with various approaches to address the bone gap. Bone transport and acute docking along with a corticotomy and distraction osteogenesis have stood the test of time. Our purpose was to evaluate the treatment outcome of the modified Ilizarov technique in infected nonunions of the femur and tibia. Methods: Twenty-six patients with infected femoral and tibial nonunions underwent aggressive debridement and either bifocal compression-distraction osteogenesis or bone transport using an Ilizarov frame. Adjuvant methods such as local antibiotic delivery systems, bone marrow aspirate concentrate (BMAC) injections, pulsatile recombinant parathyroid hormone (PTH) injections, and negative pressure wound therapy (NPWT) were deployed, as deemed necessary, in specific situations. Results: The mean follow-up period was 24.2 mo. The mean time to union was 267.7 days. Union was achieved in 25 cases with complete eradication of infection. Bone results as per the Association for Study of Application of Methods of Ilizarov (ASAMI) scoring system were excellent in 19 patients, good in four, fair in two, and poor in one. The average duration for external fixation was 8.9 mo. Complications occurred in 30.8% of patients. Conclusions: The Ilizarov method, by itself or in combination with modern methods, gives satisfactory bone and functional results. Complication rates depend upon the surgeon's adherence to the cardinal principles of Ilizarov. Level of Evidence: Level IV.